Implementation of Occupational Safety and Health (K3) Assurance for Work From Anywhere (WfA) Workers - Topic: Aspects in the Modern Work System (Case Study of PT. Reska Multi Usaha) - Muhammad Rizky Fahrezi; Abdul Razak Nasution; Hasdiana Juwita Bintang (CV. Era Digital Nusantara, 2026)
This study aims to analyze the implementation of Occupational Safety and Health (K3) guarantees for workers carrying out the Work From Anywhere (WFA) system at PT Reska Multi Usaha, as well as to identify the obstacles faced in its implementation and efforts to resolve them. This research uses a normative legal research type of a descriptive nature, examining the provisions of legislation in the field of employment and relating them to the practice of K3 implementation in flexible work systems. Research data was obtained through literature studies covering primary, secondary, and tertiary legal materials, as well as tracing relevant national regulations. The results of the study show that PT Reska Multi Usaha has implemented K3 guarantees for WFA workers through written policies based on SMK3, digital-based health and safety programs, fulfillment of BPJS Ketenagakerjaan membership obligations, an integrated incident reporting mechanism, as well as ergonomic empowerment and mental health programs for remote workers. The implementation faces several obstacles, including limited direct supervision over the work environment of WFA workers, low awareness among some workers of ergonomic and psychosocial risks, and the absence of specific regulations governing K3 in the Work From Anywhere work system comprehensively in Indonesia. Efforts to resolve these challenges are carried out through digitalization of the K3 monitoring system, strengthening of online-based education programs, and development of internal WFA K3 guidelines as a corporate self-regulation instrument. This research is expected to make an academic and practical contribution to the development of K3 policies that are adaptive to the dynamics of modern work systems.